Preassembly and independent trafficking of the exocyst complex in Arabidopsis - Su Jiang; Zhendong Liu; Shuju Zhao; Tonghui Li; Juan Li; Can Bu; Long Ma; Xiaonan Liu; Shan Gao; Guangyou Duan; Dayong Cui; Chun-Ming Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Membrane fusion, the culmination of eukaryotic membrane trafficking, is orchestrated by the exocyst complex (a conserved octamer comprising SC1 and SC2 heterotetramers) and sensitive factor attachment protein receptor (SNARE) complexes. Although trans -SNARE complex formation is essential for function, a similar trans -interaction mechanism for the exocyst remains uncertain. We employed advanced live-cell imaging combined with genetic and pharmacological techniques to dissect the spatiotemporal dynamics of exocyst subunit interactions and cargo vesicle association in Arabidopsis thaliana hypocotyl cells. Our results demonstrate that subunits from SC1 and SC2 colocalize and undergo actin-dependent transport to the plasma membrane (PM). Disruption of either SEC6 (SC1) or EXO70A1 (SC2) prevented PM association of both subcomplexes, indicating cytoplasmic preassembly of the cis -exocyst complex before PM recruitment. Critically, we found that the exocyst does not directly bind vesicles carrying cellulose synthase complexes (CSCs). Instead, exocyst subunits first migrate on CSC-negative vesicles, which then coalesce with CSC-carrying vesicles at the cell cortex via heterotypic fusion. Together, our findings reveal a parallel mechanism for exocyst assembly and cargo loading. This coordinated process may represent a broadly conserved strategy to ensure efficient membrane trafficking in eukaryotic cells.